Does corporate social responsibility lead to improved firm performance? The hidden role of financial slack. Issue 7 (8th July 2019) - Lin, Woon Leong; Ho, Jo Ann; Ng, Siew Imm; Lee, Chin
Abstract : Purpose: The purpose of this study is to investigate the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP), as the findings on the relationship have been inconsistent and have led to calls to further examine this relationship. However, instead of investigating the connection between CSR and CFP, academics have stated that a contingency viewpoint must be used for uncovering the context and conditions which catalyse the relationship between both constructs. Design/methodology/approach: This study acquired the CSR data from 100 companies listed in Fortune's most admired US companies between 2007 and 2016. These data were used to investigate the CSR–CFP link with the help of the dynamic panel data system, which is the generalised method of moments (GMM) estimator. Findings: The results indicate that CSR and CFP have a neutral relationship which characterises the effect between CFP and CSR. However, this study found that financial slack positively affected the CSR–CFP relationship, implying that companies will only benefit from CSR activities if they have excess financial resources. Originality/value: This study offers a very distinctive perspective regarding the CSR–CFP link according to the financial slack perspective.